Pilot randomized controlled trial of a game-based intervention for teaching basketball in Chinese primary school physical education - Yan, J.; Morgan, P. J.; Smith, J. J.; Chen, S.; Leahy, A. A.; Eather, N. (Journal of Sports Sciences, 2024)
This study aimed to examine the preliminary efficacy and feasibility of implementing a tailored version of the MASTER coach education programme in Chinese primary schools to support physical education (PE) teachers` basketball lesson design and delivery. A total of 20 primary schools in Beijing, China were recruited, with one PE teacher and their class (N = 715 students aged 10-13 yrs) from each school included in the study and randomly allocated to the MASTER intervention (n = 10) or control group (n = 10). Compared to the control group, a significant difference was observed in the MASTER group for the proportion of playing-form activities delivered during PE (27.65, 95% CI [20.27, 35.03]) and for teachers` perceptions of confidence (23.92, 95% CI [15.87, 31.92]) and competence (24.12, 95% CI [10.28, 24.71]) to teach. Significant differences between groups were observed for students` perceived athletic competence (3.56%; 95% CI [3.15, 3.96]), enjoyment (11.83%; 95% CI [10.98, 12.69]), well-being (8.51%; 95% CI [7.02, 10.00]), intrinsic motivation (+0.74%; 95% CI [0.30, 1.17]), introjected motivation (-2.24%; 95% CI [-2.77, -1.70]), and external motivation (-0.49%; 95% CI [-0.90, -0.08]). The MASTER programme was effective in improving teaching practices in Chinese primary schools, and in facilitating improvements in teacher and student outcomes.